Impact of pre‐eclampsia on renal outcome in sickle cell disease patients. (15th June 2021) - Boudhabhay, Idris; Boutin, Emmanuelle; Bartolucci, Pablo; Bornes, Marie‐Isabelle; Habibi, Anoosha; Lionnet, François; Hertig, Alexandre; Grimbert, Philippe; Stehlé, Thomas; El Karoui, Khalil; Sahali, Dil; Fois, Elena; et al.
Summary: The long‐term consequences of pre‐eclampsia (PrE) for renal function have never been determined in patients with sickle cell disease (SCD). Between 2008 and 2015, we screened 306 pregnancies in women with SCD and identified 40 with PrE (13%). The control group consisted of 65 pregnant SCD patients without PrE. In multivariable analysis, PrE events were associated with an increase of 1 log of lactate dehydrogenase level (adjusted odds ratio, aOR = 3·83, P  = 0·05), a decrease of 10 g/l of haemoglobin levels (aOR = 2·48, P  = 0·006) and one or more vaso‐occlusive crisis during pregnancy (aOR = 16·68, P  = 0·002). Estimated glomerular filtration rate (eGFR) was similar in the two groups at steady state but was significantly lower in the PrE group after one year of follow‐up and at last follow‐up (130 vs 148 ml/min/1·73 m 2, P  < 0·001 and 120 vs 130 ml/min/1·73 m 2, P  < 0·001, respectively). In multivariable analysis, eGFR had returned to steady‐state levels one year after pregnancy in patients without PrE but continued to decrease in patients with PrE (β = −18·15 ml/min/1·73 m 2, P  < 0·001). This decline was more marked at the end of follow‐up (β = −31·15 ml/min, P  < 0·001). In conclusion, PrE episodes are associated with a significant risk of subsequent renal function decline in SCD patients.